Prosthetic joint infection in culture-negative and alpha-defensin-positive patients versus culture-positive and alpha-defensin-negative patients: a retrospective cohort study of the differences in clinical characteristics and outcomes. Issue 1 (January 2021) - Vajapey, Sravya P.; Li, Daniel; Lynch, Daniel; Li, Mengnai
Abstract : Background: Culture-negative (CN) prosthetic joint infection (PJI) poses a challenge for the clinician for both diagnosis and management. We compared the clinical presentation and outcomes between patients with CN alpha-defensin-positive PJI and culture-positive (CP) alpha-defensin-negative PJI. Methods: This was a retrospective study of 15 patients who underwent treatment for PJI (four hips and 11 knees) at a tertiary referral center by a single surgeon from 2016 to 2019. Patients were divided into two cohorts based on their culture results: one group had negative cultures but positive alpha-defensin test (n=7) and the other had positive cultures but negative alpha-defensin test (n=8). These two cohorts were compared in terms of clinical presentation, laboratory values, treatment duration, and functional outcome. Statistical analysis was performed on variables of interest. Results: Patients in both PJI groups most commonly presented with pain and swelling of the involved joint. There was a greater proportion of CN PJI patients with a history of infection, such as bacteremia or urinary tract infection (UTI) requiring antibiotics, than CP PJI patients (42.9% vs. 0%). There was no statistically significant difference in inflammatory marker elevation for either group. Only 57% of the CN PJI patients underwent surgical debridement versus all CP PJI patients. There were no differences in outcomes at final follow-up between the two groups. Conclusions: Prior history of infection requiring antimicrobial therapy is a risk factor for negative cultures. CN PJI is not a negative prognostic indicator and results in outcomes similar to CP PJI. Level of Evidence: Level III.